Greenthrive compact high-yield hydroponics for Singapore residents - Lim, Ted Yi De (Nanyang Technological University, 2024)
This report presents an in-depth exploration of hydroponics, focusing on the development of GreenThrive, a compact high-yield vertical farming system designed for household use in HDB flats in Singapore. With inspiration from mirror designs and sustainability principles, GreenThrive aims to create a home-based hydroponic cultivation in urban environments.